The Incidence and the Risk Factors of Silent Embolic Cerebral Infarction After Coronary Angiography and Percutaneous Coronary Interventions. (May 2016) - Deveci, Onur Sinan; Celik, Aziz Inan; Ikikardes, Firat; Ozmen, Caglar; Caglıyan, Caglar Emre; Deniz, Ali; Bicakci, Kenan; Bicakci, Sebnem; Evlice, Ahmet; Demir, Turgay; Kanadasi, Mehmet; Demir, Mesut; et al.
Silent embolic cerebral infarction (SECI) is a major complication of coronary angiography (CAG) and percutaneous coronary intervention (PCI). Patients with stable coronary artery disease (CAD) who underwent CAG with or without PCI were recruited. Cerebral diffusion-weighted magnetic resonance imaging was performed for SECI within 24 hours. Clinical and angiographic characteristics were compared between patients with and without SECI. Silent embolic cerebral infarction occurred in 12 (12%) of the 101 patients. Age, total cholesterol, SYNTAX score (SS), and coronary artery bypass history were greater in the SECI(+) group (65 ± 10 vs 58 ± 11 years, P = .037; 223 ± 85 vs 173 ± 80 mg/dL, P = .048; 30.1 ± 2 vs 15 ± 3, P < .001; 4 [33.3%] vs 3 [3.3%], P = .005). The SECI was more common in the PCI group (8/24 vs 4/77, P = .01). On subanalysis, the SS was significantly higher in the SECI(+) patients in both the CAG and the PCI groups (29.3 ± 1.9 vs 15 ± 3, P < .01; 30.5 ± 1.9 vs 15.1 ± 3.2, P < .001, respectively). The risk of SECI after CAG and PCI increases with the complexity of CAD (represented by the SS). The SS is a predictor of the risk of SECI, a complication that should be considered more often after CAG.